1981
DOI: 10.1007/bf01908164
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive changes in the isoenzyme pattern of myosin from hypertrophied rat myocardium as a result of pressure overload and physical training

Abstract: The distribution of cardiac myosin isoenzymes is altered as a result of pressure overload and physical training. Using polyacrylamide gel electrophoresis in sodium pyrophosphate, it was found that myosin from left ventricles of adult rats exists in three polymorphic forms, V1, V2 and V3. Cardiac hypertrophy due to renal hypertension (Goldblatt II) led to a shift of the isoenzymes towards V3, whereas swimming training resulted in an opposite redistribution. The isoenzyme V1 predominated, only traces of V2 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

1982
1982
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(46 citation statements)
references
References 39 publications
(30 reference statements)
2
42
0
2
Order By: Relevance
“…As in numerous other investigations (2,3,8,9 and others) this study documents the sensitivity of the pyrophosphate gel technique in detecting changes in isoenzyme distribution in rat cardiac myosin. When myosins with lower ATPase activities are studied, more sensitive approaches, such as the use of monoclonal antiisoenzyme antibodies appear to be required (11), but this has not been necessary with rat cardiac myosin.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As in numerous other investigations (2,3,8,9 and others) this study documents the sensitivity of the pyrophosphate gel technique in detecting changes in isoenzyme distribution in rat cardiac myosin. When myosins with lower ATPase activities are studied, more sensitive approaches, such as the use of monoclonal antiisoenzyme antibodies appear to be required (11), but this has not been necessary with rat cardiac myosin.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, it has been observed in the rat that physiologic loads such as chronic exercise, which result in cardiac hypertrophy in the rat, may increase contractile performance (1), contractile protein ATPase activity (1), and a shift to even a greater predominance of the V1 myosin isoenzyme (3).…”
mentioning
confidence: 99%
“…It has been shown that many other pathophysiological states, including exercise (52,53), diabetes (54,55), starvation (56), high carbohydrate diet (56), adrenalectomy (56), dwarfism (57), and gonadectomy (58), can also modulate the cardiac MHC isozyme distribution. It remains to be seen whether these stimuli act independently on the expression of the MHC genes or whether their effects are mediated by a common biochemical signal.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that other physiologic and hormonal factors, such as exercise, 61 denervation, 8 hemodynamic overload, 41 a high carbohydrate diet, 12 insulin," growth hormone, 35 glucocorticoid, 12 and sex steroids 13 can also modulate MHC isoform expression in cardiac and skeletal muscles. It remains to be seen whether these various stimuli act independently on the expression of the MHC genes or whether their effects are mediated by a common final biochemical signal.…”
Section: Discussionmentioning
confidence: 99%